2022
DOI: 10.1021/acs.est.2c01739
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Atmospheric Oxidants Can Better Reduce Sulfate Aerosol in China: H2O2 Aqueous Oxidation Pathway Dominates Sulfate Formation in Haze

Abstract: Particulate sulfate is one of the most important components in the atmosphere. The observation of rapid sulfate aerosol production during haze events provoked scientific interest in the multiphase oxidation of SO 2 in aqueous aerosol particles. Diverse oxidation pathways can be enhanced or suppressed under different aerosol acidity levels and high ionic strength conditions of atmospheric aerosol. The importance of ionic strength to sulfate multiphase chemistry has been verified under laboratory conditions, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
4
31
1
1
Order By: Relevance
“…Aerosol liquid water serves as an efficient medium for multi-phase reactions (Wu et al, 2018;Yue et al, 2019), whereas the radius is negatively associated with the sulfate formation at the droplet interface (Hung et al, 2018;Chen et al, 2022). Furthermore, droplet acidity decreases as the liquid volume increases, thereby increasing the ionization of dissolved sulfur species, followed by the increased sulfate formation rate (Yue et al, 2019;Jin et al, 2020;Gao et al, 2022). Overall, how meteorological factors influence the relative importance of gas-phase, aqueous-phase, and heterogeneous pathways warrants further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol liquid water serves as an efficient medium for multi-phase reactions (Wu et al, 2018;Yue et al, 2019), whereas the radius is negatively associated with the sulfate formation at the droplet interface (Hung et al, 2018;Chen et al, 2022). Furthermore, droplet acidity decreases as the liquid volume increases, thereby increasing the ionization of dissolved sulfur species, followed by the increased sulfate formation rate (Yue et al, 2019;Jin et al, 2020;Gao et al, 2022). Overall, how meteorological factors influence the relative importance of gas-phase, aqueous-phase, and heterogeneous pathways warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…T. Wang et al: Significant formation of sulfate aerosols Tilgner et al, 2021;Gao et al, 2022;S. Wang et al, 2022;Ye et al, 2022).…”
Section: Introductionunclassified
“…The sulfate PM 2.5 concentration simulated with air quality models 13 were 3-4 times lower than that measured in the atmosphere. This gap has motivated many research efforts to discover the hitherto unidentified sulfate sources in polluted environments 11,[14][15][16][17][18][19][20][21][22] : New aqueous SO 2 conversion mechanisms have been identified, and the kinetics of existing mechanisms have been updated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sulfur isotopic evidence from SO 2 and sulfate showed that the H 2 O 2 pathway is important for sulfate formation during the first stage of haze event . In addition, the oxidation experiments and thermodynamic considerations and kinetics modeling also suggest that the H 2 O 2 pathway is enhanced during haze events due to the high solute strength of the aerosol particles and general acid catalysis effects . The H 2 O 2 in haze events can be produced from iron–HULIS complex photochemistry and aqueous microdroplets (1–20 μm in diameter) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several new pathways for rapid sulfate production in haze events have been proposed to address this issue, including aqueous oxidation of SO 2 by NO 2 , , black carbon-catalyzed sulfate formation, transition metal ions-catalyzed oxidation of SO 2 , , the heterogeneous production of hydroxymethanesulfonate by SO 2 and HCHO, enhanced sulfate formation by nitrate photolysis, and fast SO 2 oxidation by H 2 O 2 in deliquesced aerosol particles. , However, the oxidation rate of SO 2 is strongly affected by aerosol acidity (pH), ionic strength, and aerosol liquid water content, , leading to large uncertainties in the mechanisms of sulfate formation mechanism during haze events.…”
Section: Introductionmentioning
confidence: 99%